Radium-223 dichloride causes transient changes in natural killer cell population and cytotoxic function. (3rd October 2021) - Leung, Calvin N.; Howell, Donna M.; Howell, Roger W.
Abstract: Rationale: Natural killer (NK) cells play an important role in both the innate and adaptive arms of the immune system. While previous studies have demonstrated the effects of ionizing radiation on cytotoxic function of NK cells, little is known about how a chronic exposure to high LET alpha particles emitted by radionuclides will affect both NK population size and function. This study was conducted to determine the effects of 223 RaCl2 on splenic NK cell population size and function in Swiss Webster mice. Methods: Swiss Webster mice were administered intravenously with 0, 50, or 600 kBq/kg 223 RaCl2 . Spleens were harvested at 5, 12, and 19 days post-administration. The numbers of splenocytes per spleen were enumerated and flow cytometry was used to assess changes in the distribution of splenocyte subpopulations of B, CD4 and CD8 T lymphocytes, and NK cells. NK functional activity was quantified using YAC-1 target cells and the 51 Cr-release assay. Results: The total number of splenocytes was unaffected by 223 RaCl2 . However, significant changes in the distribution of splenocyte subpopulations were observed for NK cells and CD8 T lymphocytes. NK functional activity was enhanced substantially relative to controls at 12 days post-administration, but decreased markedly by day 19. Conclusion: NK functional activity is both diminished and enhanced by 223 RaCl2 depending on both administered activity and time post-administration. These results suggest that there may be an optimum window of time to combine the 223 RaCl2 -induced antitumor NK cell response with other cancer therapies that elicit immune activation.